Attitudes and experiences of health professionals towards clinical evaluations of torture and ill-treatment. (February 2021) - Moreno, Alejandro; Hor, Albert; Valencia, Victoria; Iacopino, Vincent
Abstract: Torture and ill-treatment are crimes practiced systematically in many countries around the world. Little is known about the attitudes and experiences of health professionals who evaluate the victims of these crimes. This study was conducted to assess the attitudes and experiences of health professionals who conduct clinical evaluations of alleged torture and ill-treatment and identify common needs and challenges. Two surveys were administered to health professionals who attended a series of Istanbul Protocol (IP) trainings in various countries of Central Asia, Middle East/North Africa and Latin-America. The findings indicate that participants documented a significant number of torture and ill-treatment cases during a three-year period preceding the survey and that they were interested in conducting evaluations in accordance with the IP, but expressed concern about the impact of such evaluations on their workload and the effects of secondary trauma. Participants indicated support for a wide range of professional development and self-regulatory measures. The study also indicates the need for additional training and other measures to ensure effective documentation practices as 13% of participants failed to understand one of the most basic IP concepts - that the absence of physical and/or psychological evidence does not rule out the possibility that torture and/or ill-treatment occurred. Highlights: Participants had more cases with torture findings than government figures. Participants reported a high case load (230–280 per year) for the prior 36 months. Participants expressed concerns about work schedule burden and vicarious trauma. Some continued to reject a torture allegation when clinical evidence is absent. Measures to improve investigation and documentation practices had wide supported.